(untitled) (Applied Biological Research, 2020)
The aim of present study was to initiate preliminary work on heavy metal contamination in farm soil (contaminated with processed tannery effluent) and its potential influence on the development of metal resistance among N2- fixing bacterium, Sinorhizobium sp. Contaminated plant samples were analyzed for various metals and minimum inhibitory concentration (MIC) of metals was determined. Fenugreek (Trigonella sp.) plants revealed accumulation of these metals in root and leaves. Sinorhizobium sp. were isolated (25) from the root nodules of fenugreek-treated with processed tannery wastewater and characterized morpho-biochemically. All isolates were evaluated for their resistance against Cr3+, Cr6+, Cd2+, Cu2+, Zn2+ and Ni2+. The maximum MIC of 1600 µg mL-1 was noticed against Cr3+ in 64% isolates. Among all the isolates, the lowest MIC of 25 µg mL-1 was detected against Ni2+. Some metal resistant isolates were evaluated for their resistance against frequently used antibiotics viz., tetracycline, ampicillin, gentamycin, kanamycin, chloramphenicol and nalidixic acid. About 46% Sinorhizobium isolates were resistant to nalidixic acid whereas 26.6% showed resistance to ampicillin and kanamycin. The isolates demonstrated confluent growth upto a salt concentration of 3%; whereas isolates (SM17, SM24) tolerated 10% NaCl. Acidic pH eliminated almost all the test population and neutral pH had no suppressive effect on growth while majority were tolerant to pH 9.